Numerical study of thermocoalescence of microdroplets in a microfluidic chamber - Ho, Peng Ching (2013)
The present paper reports the numerical investigation of thermocoalescence of droplets in a microchannel network consisting of a droplet formation section connecting to a temperature-induced merging chamber. The numerical model is formulated as an incompressible immiscible two-phase flow problem with oil and water as the continuous and dispersed phase, respectively. The governing equations are solved using finite volume method on a staggered mesh. The interface is captured by a narrow-band particle level-set method. The paper examines the droplet formation process and droplet size at 4 different ratios of oil and water flow rate. The motion of the droplets from the formation section into and through the heat-induced merging chamber is analyzed. The numerical method is able to provide a visual presentation of the droplet movement in a heated environment under the influence of thermocapillarity. The relationship between the critical merging temperature and the fluid flow rate is also analyzed and discussed.